Terapi Hand Massage Terhadap Tingkat Kecemasan Pada Pasien Pra Pembedahan - anggra trisna ajani; Keken Erva Nanda; Mega Adyna Movitaria; Milya Novera; Ramaita; Reska Handayani; Putri Minas Sari; Nopan Saputra; Yance Komela Sari; Aulia Asman; Shindy Gustarina (Jurnal Amanah Kesehatan, 2024)
Anxiety in the pre-operational stage reaches 534 million people, with an incidence rate of 5-25% among those aged 5-20 years and 50% among those aged 55 years and over, causing an increase in blood pressure which hinders rehabilitation efforts. One technique to reduce anxiety during surgery is hand massage. This study aims to better understand the effect of hand massage therapy on preoperative pain at RS Siti Rahmah Padang in 2023. This research is experimental in nature, using a pre-posttest design with a total of 32 samples divided equally between the intervention and control groups. The research was conducted for a full week at the Siti Rahmah Hospital in Padang Surgical Inpatient. Information was collected using the Hamilton Anxiety Rating Scale (HARS) and analyzed with the help of the Wilcoxon and Mann Whitney tests. Research based on the Wilcoxon test showed that there was a difference in symptom severity between the groups participating in the trial before and after the application of hand massage therapy (p 0.0001 for both comparisons). The results of the Mann -Whitney U test show that hand massage can reduce the level of pain experienced by surgical patients at RS Siti Rahmah Padang (p = 0.0001).